Raman lidar for monitoring of aerosol pollution in the free troposphere - Mueller, D.; Mattis, Ina; Ansmann, Albert; Wandinger, U.; Althausen, D. (Springer Nature, 2008)
Geometrical, optical, and microphysical properties of free-tropospheric pollution have been determined with multiwavelength Raman lidar at Leipzig, Germany. Long-term observations carried out at fixed times (three times per week) since 1997 show advection of different aerosol types such as anthropogenic pollution from North America, forest-fire smoke from North America and Siberia, pollution from polar areas, and Saharan dust. Up to 45% off all regular observations indicate free-tropospheric pollution. On average, 20-25% of columnar optical depth was contributed by these layers. In extreme cases, the fraction of optical depth was considerably higher. At times pollution was found around 10-12km height. Geometrical depth of the layers in many cases exceeded 1km. Mean Angstrom exponents of the layers varied from as low as 0.7 for Saharan dust to as high as 1.7 for anthropogenic pollution from North America. Individual measurements show significantly lower, respectively higher values. Lidar ratios in general were larger at 355 nm than at 532 nm. One remarkable exception is aged forest-fire smoke for which we find a reversed spectral dependence. Results for the Leipzig lidar site may be contrasted to results on European pollution outflow observed with Raman lidar at the southwest coast of Portugal. We also find strong differences with respect to South and Southeast Asian pollution observed during several field campaigns in the Indian Ocean.